English language and graduate employability - Zainuddin, Siti Zaidah; Pillai, Stefanie; Dumanig, Francisco Perlag; Phillip, Adriana (Emerald, 2019)
Purpose: The purpose of this paper is to examine the perspectives of Malaysian employers and students on the need for English language proficiency and skills for employment. Design/methodology/approach: Interviews were conducted with employers from various organisations. Additionally, questionnaires were disseminated to undergraduates at four public universities in Malaysia. These were done to ascertain the perspectives of different stakeholders on the importance of English in securing employment, the effect of a marked regional accent or dialect on employability and industry’s expectations and requirements for new employees. Findings: Employers and students agree that English plays a major role in employability. Whilst there was general agreement by both parties that good grammar and a wide range of vocabulary are important, the findings indicated several mismatches in terms of students’ perceptions and employers’ expectations. Among them is the use of the colloquial form of English at the workplace which was not favoured by employers. Employers also generally felt that knowledge of different types of writing styles could be learnt on-the-job. Furthermore, employers pointed out other essential skills for employability: the ability to communicate in other languages, confidence and a good attitude. Practical implications: Cognisant of the fact that English is essential in improving employability, initiatives to improve the level of English among Malaysian students must continue to be put in place. University students should be made aware of the different language skills sought by employers early in their university education. The mismatches between the perceptions of university students and the expectations of employers should be considered when planning English language courses and degree programmes. More structured feedback from industry on both would help to better prepare students for the world of work and to ease the transition from campus to career. Social implications: In relation to graduate employability, these English-language elite groups would have an advantage in securing employment especially in multinational companies, and this will, in a long run, create a larger gap between students from the international and public schools. Originality/value: With the standpoint of two important parties, employers and students, a more comprehensive idea of the effect of English language on employability has been obtained.